ENERGY-EFFICIENT MATERIALS: APPLICATION IN DIFFERENT FIELDS AND THEIR IMPROVEMENT - Tojiboyev Boburjon Tolibjonovich (European Science Publishing, 2024)
This article describes modern technologies in the use of energy-saving materials, the identification of materials with low thermal conductivity and the results of research conducted on them. Preparation of liquid heat-retaining materials and flawless coating on any surfaces, use of heat is covered
Keywords: Energy-saving materials, thermal conductivity analysis, requirements for energy-saving coatings, their advantages.